Photocatalytic hydrogen production from H2S using nanostructured CNT blended CdZnS/Fe2O3 thin film on glass substrate - Raja, M. Anthony; Vijayarengan, Preethi; Pal, Yash; Nalajala, Naresh; Gopinath, Chinnakonda (Journal of Physics Conference Series, 2020)
<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">A co-precipitation method was employed to prepare the CNT blended CdZnS/Fe<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">3<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> photocatalyst. Using the powder photocatalyst, the thin film of CNT blended CdZnS/Fe<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">3<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> photocatalyst over a glass substrate was prepared using the drop-casting method. The obtained thin film was characterized by X-ray diffraction (XRD), scanning electron microscope (SEM), energy-dispersive X-ray analysis (EDAX), photoluminescence (PL), and hydrogen production activity studies in order to obtain information on their structural, morphology, chemical composition, optical and hydrogen production efficiency. The hydrogen production activity of catalyst or effective conversion of H<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">S into hydrogen (H<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">) and sulfur (S) using thin-film photocatalyst was evaluated using a simulated sulfide solution. The results showed that 1 mg of CNT blended CdZnS/Fe<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">3<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> catalyst coated as thin film over glass substrate (4.69 cm<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">) showed the highest hydrogen production value of 3180 μmol h<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">−1<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">g<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">−1<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">; compared to that of 1 mg CNT blended CdZnS/Fe<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">2<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">O<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; top: 0.5ex; color: rgb(51, 51, 51);">3<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> powder of 2510 μmol h<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">−1<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">g<span style="font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; font-size: 12px; line-height: 1; font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; height: 0px; position: relative; bottom: 1ex; color: rgb(51, 51, 51);">−1<span style="color: rgb(51, 51, 51); font-family: -apple-system, BlinkMacSystemFont, "Segoe UI", Roboto, "Noto Sans", Ubuntu, "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">. From the above results, it is concluded that the thin film form of photocatlyst produced more hydrogen than the powder form. This is attributed to the effective charge separation and increased specific surface area in thin film photocatalyst.